Compulsory licensing jurisprudence in South Africa: Do we have our priorities right? - Yousuf A. Vawda (South Centre, 2018)
Compulsory licences are generally available on a variety of grounds, most notably on patents where the patentee is found to have abused its rights in one manner or another. This research paper attempts to review South African case law on applications for compulsory licences since the inception of the current legislation, analyse the interpretations placed on the relevant sections, and draw conclusions about judicial reasoning, impediments to the grant of such licences, and generally the courts' approach to disputes relating to patents.
Keywords: 300; Patentrecht; Lizenz; Rechtsprechung; Südafrika